Chewing lice (Insecta, Phthiraptera) of Bruijn’s Brush-turkey Aepypodius bruijnii (Aves, Galliformes, Megapodiidae) from New Guinea. - Mey, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 2013)
On the basis of the material examined by the author (with is very incomplete and mostly off old museum skins), the following chewing lice species known to infest Aepypodius bruijnii are here treated or described: Amblycera: Kelerimenopon aepypodi Price & Emerson, 1966 sensu lato and Talegalligogus wilhelmi waigeuensis n. ssp.; Ischnocera: Megathellipeurus mumesensis n. sp., “Oxylipeurus” aepypodius Clay, 1938, Talegallipeurus tenuis Mey, 1982, Weehalia hakalphila n. sp., and Homocerus sp. These species illustrate the close relationships between their host genera Aepypodius and Talegalla, and suggest that Alectura is more distantly related. An overview is given of the hospitalic distribution of all genera of chewing lice so far known off the Megapodiidae, with special reference to Aepypodius arfakianus and A. bruijnii. Keywords Aepypodius bruijnii, Amblycera, Ischnocera, new species & subspecies, parasitophyletic studies, Waigeo. Nomenclatural Acts mumesensis Mey, 2013 (Megathellipeurus), spec. nov. waigeuensis Mey, 2013 (Talegalligogus wilhelmi), sspec. nov. hakalphila Mey, 2013 (Weehalia), spec. nov.